2008
DOI: 10.1186/1471-2407-8-129
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HER-2 in MCF-7 breast cancer cells modulates anti-apoptotic proteins Survivin and Bcl-2 via the extracellular signal-related kinase (ERK) and phosphoinositide-3 kinase (PI3K) signalling pathways

Abstract: Background: The oncoprotein HER-2 is over-expressed and/or has undergone gene amplification in between 20 to 30% of breast and ovarian cancers. HER-2 amplified breast cancer is associated with a poor prognosis and increased resistance to chemo-and hormonal therapy. Data supporting the transforming potential of HER-2 are irrefutable but the mechanism by which HER-2 contributes to this process is complex and a unified model of HER2-induced increased cell proliferation and survival has not emerged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 29 publications
(29 reference statements)
7
77
0
1
Order By: Relevance
“…Moreover, activated growth factor signaling can provide survival signals to protect from tamoxifenand fulvestrant-induced apoptosis (Kumar et al, 1996;Chung et al, 2002;Siddiqa et al, 2008). We show herein that ARTN-stimulated resistance to antiestrogen is mediated by upregulation of BCL-2 protein expression.…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, activated growth factor signaling can provide survival signals to protect from tamoxifenand fulvestrant-induced apoptosis (Kumar et al, 1996;Chung et al, 2002;Siddiqa et al, 2008). We show herein that ARTN-stimulated resistance to antiestrogen is mediated by upregulation of BCL-2 protein expression.…”
Section: Discussionsupporting
confidence: 50%
“…We focused on Bcl-xL and survivin, both of which are reported to be induced via phosphorylation of ERK pathway (33)(34)(35)(36)(37). We showed that CCL11 increased Bcl-xL and survivin expression in Ki-JK cells in vitro (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These molecular mechanism might be occurred by suppression of survivin protein expression through inhibition of its upstream protein, HER-2 and IKK. Inhibition of HER-2 and IKK could suppress the Pgp expression that correlated to resistance breast cancer cell induced by chemotherapeutic agent, doxorubicin (Siddiqa, et al, 2008;Gilmore, 2006).…”
Section: (A) (B) (C) (D) (E)mentioning
confidence: 99%